Pertanggungjawaban Pidana Bagi Pihak Marketplace dan Penjual dalam Jual Beli Obat Ilegal Jenis Cytotec Secara Online - Maulana, Daud Abdan; Suryokencono, Pramukhtiko (Indonesian Journal of Law and Justice, 2023)
Indonesian society, especially those in urban areas, is inseparable from the internet, because almost all activities always involve the internet and information technology. So, it is not surprising that the internet has now become a basic necessity for some groups, especially for those who use the internet for business purposes (E-commerce). One of the online suggestions for selling illegal drugs is E-commerce as access to transactions via online media. Through these trade transactions, conventional buying and selling is no longer valid, and E-commerce has become an alternative trade for consumers. What is the responsibility of the marketplace and sellers in the illegal buying and selling of Cytotec hard drugs online. The type of research used is normative juridical (legal research). using a statutory approach and a case approach. In this research, researchers found that the marketplace has criminal responsibility for buying and selling illegal drugs such as misoprostol online. Based on an analysis of applicable laws and regulations, it was found that the marketplace has an obligation to monitor and prevent illegal drug buying and selling transactions on its platform. This research concludes that the marketplace is criminally responsible for buying and selling illegal drugs such as misoprostol online. Research findings show that marketplaces have an obligation to monitor and prevent illegal drug sales transactions on their platforms. However, in several cases studied, there is strong evidence that marketplaces do not take adequate steps to prevent the sale of illegal drugs, such as a lack of seller verification mechanisms, monitoring of unlawful advertisements, and a disinterest in removing illegal drug offers.